A Russian Challenge to Multipolarity?: The Prospects for Political Cooperation between Russia and Latin America. Issue 6 (2nd November 2018) - Pavlova, Elena
Abstract : This article focuses on the attitudes in Latin American countries toward Russia's newly assertive foreign policies since the annexation of Crimea. Without trying to analyze the Ukrainian events as such, this article describes the concerns of Latin American intellectual and political elites about the consequences of the crisis for the structure of the contemporary international system, which is seen as multipolar. The potential decline of multipolarity is presented in the Latin American debate as a serious problem, and both the West and Russia are blamed for this trend. Coupled with other issues, these disagreements may have a detrimental effect on Russia's relations with Latin American states.